The Economic Growth Resilience Analysis Of Papua Province During The Covid-19 Pandemic - Robert M. WST. Marbun; Charley M. Bisai (Universitas Cenderawasih, 2021)
This study is: 1) To analyze the economic growth trends (GRDP on the basis of 2010 constant prices) of Papua Province during the Covid-19 pandemic, namely from 2020 to 2021. 2) To compare the economic growth of Papua province with other provinces during the period. This study used secondary data obtained through the website of the Central Statistics Agency, as well as Bank Indonesia. The analytical method used in this study is a qualitative descriptive analysis. The research employs literature review to retrieve data, as well as referrals from various sources to support the study. The results show that: 1) GRDP growth rate from 2010 to 2020 was 2.39 percent, and 15.11 percent in 2021. In comparison with 2019, the growth is -15.74 percent, significantly higher than 2019. 2) Papua's economic growth exceeds that of other provinces in Indonesia. Supported by the primary sector, namely mining and quarrying, which expanded by a substantial amount of 29.92 percent. In addition to the primary sector, the tertiary sector also contributes to growth, namely information and communication (5.35 percent), health services (5.17 percent), and the secondary sector, which grew by 3.84 percent.Keywords: Economic growth rate, GRDP, Covid-19.